Multi-domain Orchestration leveraging the Application-Layer Traffic Optimization Protocol - Perez, Danny Alex Lachos; Rothenberg, Christian Esteve (Anais do Workshop Pré-IETF (WPIETF), 2018)
Evolving 5G network scenarios will have to deal with new multiple administrative domain (aka multi-domain) orchestration models. Based on a new broker-plane approach on top of per-domain management and orchestration functions, we present a Multi-domain orchestration prototype capable to coordinate the delivery of a multi-operator End-to-End Network Service (E2ENS) that combines per-domain paths and network functions for a given service request. Our prototype implementation retrieves local information about topology and resources from each Multi-domain Orchestrator (MdO) to offer after inter-domain added value services in the form of abstract Map Services. These map abstractions are easily consumable through developer-friendly REST APIs based on the Application-Layer Traffic Optimization (ALTO) standard protocol.